The production of degradable bioplastic from taro starch (colocasia esculenta) / Siti Zulaikha Abu Hassan - Abu Hassan, Siti Zulaikha (2020)
The rising of traditional plastic uses will caused horrible impact to the ecosystem. This is because it can lead to the plastic pollution and in some cases, it can cause the diseases because of the toxic that contained in it. By using the degradable bioplastic instead of a traditional plastic, it might help in reducing the pollution and the risk of diseases. Thus, this research aimed to extract the taro starch (Colocasia esculenta) and to produce the degradable bioplastic. Starch was extracted by manual peeling, chopping, blending, filtering and drying. Degradable bioplastic were produced from different concentration of glycerine (80%, 60% and 40%). 0.5% (w/v) of chitosan also added to act as plasticizer. Result showed that the higher the concentration of glycerine, the lower the tensile strength (MPa). Meanwhile, at slightly low concentration of glycerine (60%), it showed the highest percentage of water absorption. Furthermore, in degradation test for degradable bioplastic, it showed that the high concentration of glycerine (60% and 80%) are faster to decompose.